Convergence of Home-based Enterprises with Domestic Spaces: Evidence from Dhaka Neighborhoods (International Journal of Built Environment and Sustainability, 2017)
This research inspects the utilization of domestic space management in marginalized slums of Bangladesh towards comprehending the contribution of urban poor women’s informal employment as a private initiative. The components that influence the physical association of “home-based enterprises” (HBEs) spaces and its quality are assessed concerning the survival pattern of the low-income occupants. Further, the neighborhood and housing attributes, cultural and social, and the financial status of individuals living in slums are analyzed by in-depth interviews with questionnaires. A stratified random sampling method was used to choose 44 households in two notable neighborhoods in Dhaka City. Data was elicited through focus groups of inhabitants using qualitative research method. Thus, structured and open-ended interviews were conducted with household female members who are 18 years and above while participant observation at moderate level ensured the trustworthiness of the data. The differences observed quality and features of spaces in those settlements inhabited by the slum dwellers gave insight on the factors. The study discovered the prospect of women’s domestic spaces of home-based work in their dwelling spaces. Thereafter, the research recommends that future interferences should counter critically to the event of participation and strife contributing towards uplifting women’s situation inside a specific dwelling.